Isoflurane-lipid emulsion injection as an anticonvulsant and neuroprotectant treatment for nerve agent exposure - Krishnan, Jishnu K. S.; Moffett, John R.; Puthillathu, Narayanan; Johnson, Erik A.; Namboodiri, Aryan M. (Frontiers in Pharmacology, 2024)
We have shown that briefly inhaled isoflurane rapidly halts convulsions and protects the central nervous system (CNS) from organophosphate-induced neuronal loss when administered at 5% for 5 minutes, even as late as 1 hour after the nerve agent exposure. In the current study we investigated if an injectable form of isoflurane was as effective as inhaled isoflurane. We used a mixture of 10% isoflurane dissolved in an IV-compatible lipid-water emulsion for intravenous administration. Rats with an implanted jugular vein cannula were infused with 1000 microliters of the 10% isoflurane-lipid emulsion (ILE) mixture at a rate of 200 microliters per minute, which achieved full anesthesia lasting approximately 10 minutes. When administered 30 minutes after a highly lethal dose of the organophosphate insecticide paraoxon (POX), the short-duration administration halted convulsions permanently and prevented the great majority of neuronal loss as shown by Fluoro-Jade B staining (FJB). Our results indicate that injectable isoflurane is very effective for treating organophosphate poisoning, negating the need for vaporizer equipment and enabling intravenous therapy.